The Evaluation of Customer Satisfaction Survey Follow-Up in LPPOM MUI - Hendra Utama; Sukardi Sukardi; Taufik Djatna (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
Customer satisfaction survey is a standard method used by service providers in order to obtain feedback from the customer as well as close the gap between customer expectation and perception of service quality. Feedback from customers can make them possible to define the level of quality of service by themselves. If a service provider can satisfy its customers, it means that it will retain its customers. LPPOM MUI, as an authorized halal certifying body in Indonesia, has conducted a customer satisfaction survey three times from 2015 up to 2017. After conducting the survey, LPPOM also performed a follow-up based on the result of the survey. The purposes of this research are (1) to get to know about the follow-up of customer satisfaction evaluation of LPPOM MUI, (2) to analyze the impact of the follow-up implementation progress versus re-evaluation by LPPOM MUI’s customer group on the follow-up, (3) to provide recommendation(s) if the customers perceive the follow-up implementation still does not fulfill their service quality expectation. The methods used were a qualitative analysis based on the follow-up of LPPOM MUI’s customer satisfaction survey versus re-evaluation on LPPOM MUI’s seven customer groups on the follow-up. The result shows that all quality service attributes need improvement to meet customer expectations. They are namely 1) the ease of contacting the Call Center 14056 or LPPOM MUI, 2a) The availability of notification if any change or dysfunction of CEROL SS-23000 and 2b) replying time to customer email (3a) Dealing time to halal certification process (3b) dealing time to post-audit stage (3c) Dealing time to LPPOM MUI approval of new material of the company. Keywords: service quality, customer satisfaction survey, follow-up, LPPOM MUI, re-evaluation